Competition of External Players for Transport and Logistics Projects in Western and North Africa (on the Example of Sea Ports - M. A. Volodina (Сравнительная политика, 2020)
The paper examines the role of maritime transport in the economic development of the African continent. It is shown that the modernization of seaports not only attracts potential investors, but also opens up new opportunities for African countries. Thanks to the creation of new innovative ports, new jobs are created, training programs appear, and the local population is more actively involved in new technologies. Foreign companies often offer a set of measures to reform the transport and logistics sstems of African countries, with the connection of all transport arteries for faster delivery of goods. There are a number of problems that hinder the implementation of ambitious logistics projects, but with the joint efforts of foreign representatives and local authorities, it is possible to gradually reform legislation, prepare transport solutions taking into account the specifics of each country, and improve the investment attractiveness of African countries. Projects implemented in North and West Africa reflect different approaches of the world's leading countries to foreign economic strategy. The main competitors in the fight for new projects in Africa are Western countries, on the one hand, and China, on the other. Sea transport is the oldest transport link in Africa, and many ports were built by the efforts of the colonial authorities. Some ports have a narrow commodity specialization, which hinders the development of sea traffic. New innovative ports are needed for successful trade operations in Africa. In some countries, the solution of transport and logistics problems was dictated by economic and industrial needs. For example, in Morocco, the construction of automobile factories (with the need for subsequent transportation of finished products) has prompted foreign companies to develop a plan for an innovative industrial city with a modern port. In general, in many countries, the process of modernizing transport and logistics systems is still in its infancy, but ports have become the starting point for new investment programs for systemic transformation in Africa.